QUASI-DIURNAL ATMOSPHERIC AND OCEANIC EXCITATION OF NUTATION - Vondrák J.; Ron C. (My University, 2007)
The periodic motion of the Earth's spin axis in space (nutation) is dominantly forced by external torques exerted by the Moon,Sun and planets. On the other hand, long-periodic geophysical forces (with periods longer than several days), mostly causedby the changes in the atmosphere and oceans, have dominant effects in polar motion (in terrestrial frame) and Earth's speed ofrotation. However, even relatively small short-periodic (near-diurnal) motions of the atmosphere and oceans can also have a non-negligible influence on nutation, thanks to the resonance that is due to the existence of a flattened outer fluid core. Theretrograde period, corresponding to this resonance, is roughly equal to 430 days in non-rotating quasi-inertial celestial reference frame, or 23h 53min (mean solar time) in the terrestrial frame rotating with the Earth. The aim of the present studyis to use the geophysical excitations in the vicinity of this resonance to estimate their influence on nutation, based on recent models of atmospheric and oceanic motions. To this end, we use the numerical integration of Brzezinski's broad-band Liouville equations and compare the results with VLBI observations. Our study shows that the atmospheric plus oceanic effects (both matter and motion terms) are capable of exciting free core nutation; both its amplitude and phase are compatiblewith the observed motion. Annual and semi-annual geophysical contributions of nutation are of the order of 100microarcseconds. They are slightly different for different atmospheric/oceanic models used, and they also differ from thevalues observed by VLBI – the differences exceed several times their formal uncertainties.
Keywords: EARTH ORIENTATION; GEOPHYSICAL EXCITATION; NUTATION; VLBI